PENGARUH LATIHAN RELAY DRIBBLE DENGAN CEPAT TERHADAP KECEPATAN DRIBBLE TIM SEPAKBOLA SMAN 1 LUBUK DALAM - H Sinaga, Rinaldo Agus; Slamet, Slamet; Wijayanti, Ni Putu Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on the analysis carried out, throughout the research conducted by researchers when they encountered problems with the dribble ability of SMAN 1 Lubuk Dalam football team players who were not fast and good so that they could be easily captured by opposing players which led to the failure of the attack, the researchers began researching and provide a fast Dribble Relay exercise that begins with a free test to prove the influence of the exercise being implemented.As for population and sample here is SMAN 1 Lubuk Dalam football team. By using the ball dribbling speed test instrument then descriptive analysis was carried out and the liliefors test produced a normal data.Based on data obtained after and before the exercise, the t-count between the initial test and the final test of the Dribble Relay exercise on dribble speed shows a number of 4.941. Furthermore, the value obtained is compared with the table at the 0.05 significance level with the degree of freedom N-1 (15) turned out to show the number 1.753, this indicates that the value of tcount (4.941)> t table (1.753), it can be concluded that the hypothesis states the effect of the Dribble Relay exercise on the Dribble Speed of the SMAN 1 Football Team Lubuk Dalam. Based on the results of the analysis, it can be summarized as follows: Related to dribble relay exercise on the speed (X) on dribbling speed (Y) in SMAN 1 Lubuk Dalam football team. Key Words: Fast Dribble Relay On Dribble Speed